Antioxidant Peptides from Miiuy Croaker Swim Bladders: Ameliorating Effect and Mechanism in NAFLD Cell Model through Regulation of Hypolipidemic and Antioxidant Capacity - Yu-Mei Wang; Ming-Xue Ge; Su-Zhen Ran; Xin Pan; Chang-Feng Chi; Bin Wang (Marine Drugs)
In this work, the hypolipidemic and antioxidative capacity of FSGLR (S7) and GIEWA (S10) from miiuy croaker swim bladders was explored systematically in an oleic acid (OA)-induced nonalcoholic fatty liver disease (NAFLD) model of HepG2 cells. Moreover, the hypolipidemic activity of S7 and S10 and their antioxidative abilities were preliminarily investigated in combination with molecular docking technology. The results indicated that S7 and S10 could decrease the amount of lipid accumulation and the content of triglycerides (TG) and total cholesterol (TC) in the OA-induced NAFLD cell model in a dose-dependent manner. In addition, S7 and S10 exhibited better bile salt binding, pancreatic lipase (PL) inhibition, and cholesterol esterase (CE) inhibition capacities. The hypolipidemic mechanisms of S7 and S10 were connected with the downregulation of the mRNA expression levels of adipogenic factors, including sterol-regulatory element-binding protein-1c (SREBP-1c), acetyl-CoA carboxylase (ACC), sterol-regulatory element-binding protein (SREBP)-2, hydroxymethylglutaryl-CoA reductase (HMGR), and fatty acid synthase (FAS) (p < 0.01), and the upregulation of the mRNA expression of β-oxidation-related factors, including carnitine palmitoyltransferase 1 (CPT-1), acyl-CoA oxidase 1 (ACOX-1), and peroxisome proliferator-activated receptor α (PPARα). Moreover, FSGLR (S7) and GIEWA (S10) could significantly protect HepG2 cells against OA-induced oxidative damage, and their antioxidant mechanisms were related to the increased activity of intracellular antioxidant proteases (superoxide dismutase, SOD; glutathione peroxidase, GSH-PX; catalase, CAT) to remove excess reactive oxygen species (ROS) and decrease the production of malondialdehyde (MDA). The presented findings indicate that the hypolipidemic and antioxidant functions and mechanisms of S7 and S10 could make them potential hypolipidemic and antioxidant candidates for the treatment of NAFLD.